A case of primary antiphospholipid syndrome under the mask of systemic lupus erythematosus - N. S. Pozhilenko; T. V. Moiseeva (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2022)
A case of late diagnosis of primary antiphospholipid syndrome in a patient with recurrent miscarriage is presented. The pronounced immunological activity of the antiphospholipid syndrome with severe arthritis, fibrosing alveolitis mimicked systemic lupus erythematosus.